(3cJGH RgQGhj aj GdWH hGdLQGMIs - (3CHhGdbGSe Nda Hf YHGS GdRgQGhj GdWHjH, GdRgQGhj,J (B427 (3g` s
(3ChdgG (B:s
(3bGd hGVM gPG GdcJGH deG GcedJ dce eG Hfj gPG GdcJGH GdPi gh LRA ef GdYde ef GdWH HceGdg hHdZJ GdZGjI ef hVhMg s
(3BNQgG (B:s
(3Ke Md GdTO hVY Ydi GdehVY GdaUO bWfg hSO GdehVY aEfg jHQC SQjYkG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B674s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs